Circular RNA Circ0021205 Promotes Cholangiocarcinoma Progression Through MiR-204-5p/RAB22A Axis - Tu, Jianfei; Chen, Weiqian; Zheng, Liyun; Fang, Shiji; Zhang, Dengke; Kong, Chunli; Yang, Yang; Qiu, Rongfang; Zhao, Zhongwei; Lu, Chenying; Lu, Xiaojie; Ji, Jiansong (Frontiers in Cell and Developmental Biology, 2021)
Cholangiocarcinomas (CCA) are biliary tract tumors that are often challenging to diagnosis and treatment. Accumulated evidence reveals that circular RNAs (circRNAs) are involved in multiple cancer progression. However, the function of circRNAs in cholangiocarcinoma remains largely unclear. In this study, we found that circ_0021205 expression was upregulated in CCA and positively correlated with tumor size and TNM stage. To further explore the role of circ_0021205 in CCA, cell functional assays were performed. The results showed that circ_0021205 promoted the proliferation, migration, and invasion of CCA cells. In vivo experiments showed that circ_0021205 inhibition reduced tumorigenesis in mice. In addition, mechanisms investigation demonstrated that circ_0021205 exerts its oncogenic function by sponging miR-204-5p to regulate the expression of RAB22A. Overall, this study revealed that circ_0021205 might serve as a potential diagnostic biomarker or therapeutic target for CCA.